(untitled) (Archaeologia Adriatica, 2026)
In 2013 a recreational diver from Brbinj discovered an underwater archaeological site in Lučina Bay by the settlement of Brbinj on the island of Dugi Otok. He notified archaeologists from the International Centre for Underwater Archaeology in Zadar, who confirmed that the site dates to the modern era. Most of the recovered archaeological material consists of remains of building elements such as brick and mortar, as well as numerous fragments of pottery, glass, tobacco pipes and other small artefacts. Over the course of three archaeological campaigns the site was investigated and documented in its entirety. It was established that the deposit represents heterogeneous refuse that was probably used to stabilise a vessel during navigation, after which it was dumped in Lučina Bay prior to the loading of cargo. The finds date the site to early in the second half of the 18th century.